2010
DOI: 10.1007/s00421-010-1482-y
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of performance in human locomotion

Abstract: This paper reports an analysis of the principles underlying human performances on the basis of the work initiated by Pietro Enrico di Prampero. Starting from the concept that the maximal speed that can be attained over a given distance with a given locomotion mode is directly proportional to the maximal sustainable power and inversely proportional to the energy cost of locomotion, we discuss the maximal powers (and capacities) of anaerobic (lactic and alactic) and aerobic metabolisms and the factors that limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 69 publications
(81 reference statements)
0
24
0
Order By: Relevance
“…maximal oxygen uptake ( V O )), 4,5 V O at the lactate threshold, 4,6 and the efficiency with which metabolic energy is transferred into effective power output (PO). [7][8][9][10] During relatively short competitive events (less than ~10 min) there is also an anaerobic contribution to energy expenditure, which needs to be accounted for. 3,11,12 For example, Foster et al 13 found that the relative contribution of anaerobic energy expenditure to total work done during a 3000 m time trial was 30%.…”
Section: Introductionmentioning
confidence: 99%
“…maximal oxygen uptake ( V O )), 4,5 V O at the lactate threshold, 4,6 and the efficiency with which metabolic energy is transferred into effective power output (PO). [7][8][9][10] During relatively short competitive events (less than ~10 min) there is also an anaerobic contribution to energy expenditure, which needs to be accounted for. 3,11,12 For example, Foster et al 13 found that the relative contribution of anaerobic energy expenditure to total work done during a 3000 m time trial was 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Ceteris paribus, P D is directly proportional to C x , so that dynamically favourable shapes are characterized by low C x values, as is the case for aerodynamic contemporary cars or track bicycles used for record trials (Capelli et al 1993; di Prampero 2000) (see Fig. 2.11) Since D is a force, in analogy with C, it can be expressed as mechanical work per unit of distance (Ferretti et al 2011), so that…”
Section: Energy Cost Of Locomotionmentioning
confidence: 98%
“…But walking, with respect to all other types of locomotion, is peculiar, because of the effects of pendulum-like mechanism and the ensuing transformation of potential energy into kinetic energy and vice versa. Concerning running, C was generally considered invariant in a given individual and thus independent of the running speed (di Prampero 1986;Ferretti et al 2011), possibly as a consequence of the fact that most data were obtained during treadmill running, a condition in which the running human moves with respect to the treadmill's belt, but not with respect to air (Dill 1965;di Prampero et al 1986;Hagberg and Coyle 1984;Helgerud 1994;Margaria et al 1963;McMiken and Daniels 1976;Minetti et al 2002;Padilla et al 1992, to give a few examples). Yet Pugh (1970) demonstrated that a fraction of C varies with the square of wind velocity, although this fraction was considered small.…”
Section: Energy Cost Of Locomotionmentioning
confidence: 99%
“…P max is defined as the apex of the P ext -cadence relationship at a specific performance level and C opt is defined as the specific value at which P max occurs (Dorel et al 2005(Dorel et al , 2010Emanuele and Denoth 2011;Hintzy et al 1999;Martin et al 1997). It is clear that the longer the given race distance, the lower the sustainable P max , respectively, the sustainable performance level will be (di Prampero 2003;Ferretti et al 2011). Thus, P max in a short-term sprint cycling performance is by a multiple greater than P max in an endurance cycling performance.…”
Section: Introductionmentioning
confidence: 99%